Efektivitas Penerapan Model Pembelajaran Konflik Kognitif Berbasis Laboratorium Mini Dalam Pembelajaran Fisika - Fahima Muhlis (Peneliti.net, 2018)
This research aimed at investigating effectiveness of mini lab based cognitive conflict model application in physics learning on context, process and result components. This research used two types of data; they were primary data gained through observation and interview, and secondary data gained through documentation study. The instruments of research were interview guideline and observation sheet that was validated by using Aiken’s validation formula. The result in context component showed that teacher had fulfilled all criteria appropriately. It can be observed by the fulfillment of indicator of preparing syllabus, lesson plan, material characteristic and learning media. The result of process component showed that teacher and student had fulfilled process component well include indicator of student’s orientation in conflict, indicator of organizing students to learn, indicator of guiding individual and group investigation, indicator of developing and presenting the work, indicator of analyzing and evaluating. The result of result component showed that teacher was able to create learning evaluation properly. It showed by carried out of student’s cognitive learning achievement, the indicator of effective learning achievement, and the indicator of psychomotor leaning achievement. The conclusion of this research that mini lab based cognitive conflict model application in physics learning in context component, process and result is effective. Thus, mini lab based cognitive conflict model application in can be used in physics learning because it has been test it’s effectiveness.